Antitumour activity of a combined treatment with PMEDAP and docetaxel in the Prague inbred Sprague-Dawley/cub rat strain bearing T-cell lymphoma - Bobková, Klára; Gut, Ivan; Mandys, Václav; Holý, Antonín; Votruba, Ivan; Otová, Berta (Anticancer research, 2001)
Antitumour efficiency of combined therapy with N-9-[2-(phosphonomethoxy)ethyl]-2,6-diaminopurine (PMEDAP) and docetaxel (DTX) was studied in an in vivo model of s.c. transplanted Sprague-Dawley (SD/Cub) rat T-cell lymphoma (phenotype SD10/96). The effect of the combined treatment of DTX with PMEDAP was significantly higher than that of DTX or PMEDAP alone. The s.c. administration of DXT into the vicinity of growing lymphoma together with i.p. administration of PMEDAP was found to be the most efficient combination. In this case, two out of four rats did not develop any lymphoma and remained alive. An irregular expression of Bcl2 protein was found in untreated and treated lymphomas, while the expression of protein p53 as well as MDM2 was not observed. All three types of the above-mentioned treatments (PMEDAP, DXT, DXT+PMEDAP) increased significantly the number of p21-positive cells, compared with untreated tumours.
Keywords: paclitaxel; krysa rodu Rattus; mužské pohlaví; Antineoplastic Agents, Phytogenic; Injections, Intraperitoneal; Male; synergismus léků; Female; Injections, Subcutaneous; transplantace nádorů; fytogenní protinádorové látky; Neoplasm Transplantation; injekce intraperitoneální; taxoidy; ženské pohlaví; modely nemocí na zvířatech; Rats; Adenine; Antineoplastic Combined Chemotherapy Protocols; lymfom T-buněčný; Animals; zvířata; Taxoids; protokoly protinádorové kombinované chemoterapie; Drug Synergism; Lymphoma, T-Cell; Rats, Sprague-Dawley; injekce subkutánní; Disease Models, Animal; adenin; potkani Sprague-Dawley; Paclitaxel